Anthropometric Measurements to Detect Stunting in Toddlers in Plosokerep Village, Sragen - Arimbi, Cindy Kartika; Ramahandika, Achmad Kukuh; Sukmawati, Andera Prastina; Latif, Syariah; Radinda, Indiana; Kurniawati, Innie; Zahra, Izdihar; Hizza, Rifqi Warnedi; Saputra, Andi; Pristianto, Arif; Naufal, Adnan Faris (Urecol Journal. Part C: Health Sciences, 2023)
Short Toddler (Stunting) is the nutritional status based on the PB/U or TB/U index where in anthropometric standards to assess the nutritional status of children, the measurement results are at the threshold (Z-Score) < -2 SD to -3 SD (short/dwarf) and <-3 SD (very short/severe stunted). Stunting is a health problem that occurs in society so it needs to be treated seriously, because it will have an impact in the long term and can be repeated in the life cycle. The direct cause of stunting is malnutrition in toddlers which can have an impact on low levels of intelligence. This education aims to provide knowledge to parents about stunting prevention and how to overcome stunting in toddlers. Thus, this education is very important because in cases of increased stunting, problems with growth and development in children can be prevented and minimize further disability in sufferers of stunting. In this counseling, it was found that there were a number of toddlers who experienced stunting or malnutrition, namely as many as 6 toddlers and from head circumference measurements, the results of toddlers with microcephaly head circumference (small head circumference) were 7 toddlers (29%).